FACTORS AFFECTING CAREER ADVANCEMENT OF TOP LEVEL OF WOMEN IN LOCALLY OPERATED COMMERCIAL BANKS IN COLOMBO - Perera, M.I.D. (University of Jaffna, 2019)
In recent years, career of the women has to turn into a significant area of concern, and during the last two decades, there has been an increase in the proportion of women at entry and middle-level management positions according to the census and statistic department. According to the Central Bank report in 2017, there was a decline in the female and youth unemployment rates during 2017. The female unemployment rate declined from 7% in 2016 to 6.5% in 2017, and due to the decline in the unemployment rate, labour force participation rate among females increased from35.9% in 2016 to 36.6% in 2017. In this background, this study aims to identify the factors influencing the career advancement of top-level women who are working in locally operated commercial banks in Colombo district. It was focused on selected 12 commercial banks of out of 24, and from each bank, ten women workers selected randomly in 2017. A semi-structured questionnaire was issued to the total sample of 120 respondents to collect the relevant data related to women career advancement, which are categorized into three levels, and it was considered as an ordinal dependent variable. Other data related to four variables, such as organizational factors, personal factors, family factors, and cultural factors also collected, and they were used as explanatory variables in the study. The collected data were analyzed using econometrics techniques such as the ordered probit model and marginal effects. Results show that among the four variables, personal factors are the most critical determinant while organizational and cultural factors are the most influential factor in career advancement among top-level women in the locally operated commercial banks, respectively.
Keywords: Banking Industry; Career-Focused Top-Level Women and Women Career Advancement